Study on adsorption of Cu(II)–Cr(VI) binary system by carbonized Eupatorium adenophorum. Issue 5 (23rd March 2016) - Chen, Jinfa; Song, Dagang; Yang, Peng
ABSTRACT: We first report a mechanism study on the adsorption of Cu(II)-Cr(VI) binary mixture by a novel low-cost adsorbent, carbonized Eupatorium adenophorum. The influences by pH value, dosage, initial concentration, temperature, and adsorption time on its performance to absorb copper and chromium were investigated. The experimental data were fitted according to the Langmuir and Freundlich adsorption isotherm models, the pseudo-first-order kinetics, the pseudo-second-order kinetics, and the intra-particle diffusion model. The results indicated that when the reaction system was with its pH = 5, the dosage of carbonized Eupatorium adenophorum was 0.1 g, the adsorption time was 30 min, and the temperature was 25°C; the adsorption capacities for Cu(II) and Cr(VI) reached 27.62 mg/g and 9.68 mg/g, respectively. The process of carbonized Eupatorium adenophorum to absorb Cr(VI) is also accompanied by redox reactions. The Langmuir model and the pseudo-second-order model can better ﬁt the experimental data. Observation by fourier transform infrared spectroscopy (FTIR) and scanning electron microscope (SEM) found no significant change of functional groups before and after the adsorption by carbonized Eupatorium adenophorum, and this adsorption process is mainly a physical adsorption.